Design and evaluation of digital platforms for teaching mathematics to students with ASD and ADHD - Gallardo Herrerías, Celia (PEM. Revista de Didáctica, Evaluación e Innovación, 2025)
This study explores the design and evaluation of an e-learning platform for the education of students with Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD) in mathematics. The platform integrates accessibility, gamification, and adaptive learning for overcoming cognitive, emotional, and sensory challenges. A mixed-methods design was employed, including pre- and post-intervention measurements, observation, and feedback from students, teachers, and parents. Results were impressive: mathematics performance averaged 30% higher, students were correctly answering problems in larger numbers. Interactive and graphical presentation of the platform reduced stress and frustration, as reported by 71% of the students who exhibited positive affect for mathematics activities following treatment. Gamification elements substantially enhanced motivation, particularly for ADHD students, with an 80% engagement rate for instant feedback. ASD students benefited from highly structured, predictable interfaces, with a 65% reduction in anxiety incidents.
Keywords: Digital learning platform; Neurodiverse education; Mathematics instruction; Inclusive design